Tờ trình tóm tắt đề xuất chủ trương đầu tư Chương trình mục tiêu quốc gia giảm nghèo bền vững giai đoạn 2021-2025 - Chính phủ (2021)
Toàn văn Tờ trình tóm tắt đề xuất chủ trương đầu tư Chương trình mục tiêu quốc gia giảm nghèo bền vững giai đoạn 2021-2025